Answer:
6 + 2g
Step-by-step explanation:
whenever you have a problem like that you have to distribute the 2 to both the numbers in the parenthesis. You have to multiply 2 by 3 which is 6. Then you multiply 2 by g and you get 2g. We can't get any further so the simplified expression would be 6 + 2g
We know that
case 1) -10/-7-----> 10/7-------> is not <span>equivalent to -10/7
case 2) </span>-3 1/7----> (-3*7+1)/7----> -20/7 ------> is not equivalent to -10/7
case 3) 1 3/7-----> (1*7+3)/7----> 10/7 ------> is not equivalent to -10/7
case 4) - -10/-7---> +10/-7----> -10/7------> is equivalent to -10/7
case 5) -1 3/7----> (-1*7+3)/7----> -4/7 ------> is not equivalent to -10/7
the answer is
- -10/-7
Answer:
a) Angle X = 108°
<h3>C). Vertically opposite angles</h3>
as AD is parallel to EH both the angles are equal